(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It has always been a point of exchange of views whether art should purely be for art’s sake or there should be a specific aim behind it. Right from the times of Plato to the present times, this controversy still persists. Plato held the view that art serves no useful purpose, that it waters emotions, and that instead of feeding the audience on truth, it takes men away from reality. It is clear that he was motivated by a moral purpose. He regarded imitation as mere mimesis or servile copying not an expression which is creative. Aristotle his disciple, tried to free poetry from Plato’s charge. He said that poetry is not a servile representation of the surface or appearance but a representation of the passions and emotions of men. In his view, “It is not the function of the poet to relate what has happened but what may happen – according to the laws of probability and necessity”. Later Horace, a Roman poet, added something more to what Aristotle had said. He said that a poet often uses fiction and mingles facts with fancy. The function of poetry to him was not a servile imitation but an imitation with the purpose of delight and instruct. Thus the concept of art as imitation had, therefore, begun to hold less importance. In the history of literature the change in the concept of art is clearly indicated by the first classic of English criticism The Apologie for Poetry written by Sir Philip Sydney (1554-1586), in 1580s. Sidney also accepted the concept of art as imitation, which was introduced by Aristotle. He does agree with Aristotle that imitation not only means mere copying or a reproduction of facts but also a representation or transmutation of the real and the actual, and sometimes creating something entirely new. But where Aristotle does not clearly express his views about the purpose of art, Sidney affirms that art has a dual purpose to delight and teach. He further says that in order to teach and delight, poets imitate not ‘what is, hath been or shall be’ but only ‘what may be’ and should be as that the very objects of imitation become such as to guarantee the moral purpose. Next to Sidney it was Ben Jonson (1573?-1637) who regarded poetry as a great civilizing force. Poetry according to him offers to mankind a certain rule, the pattern of living well and happily.